Information System for Transaction Activities in a Company - A Darmayadi; L Nurfitriyanti; A J Khaira; N P Dewi (International Journal of Education, Information Technology, and Others, 2021)
This research aims to create a computerized system that the company can use in carrying out the company's operational activities, which requires information. The methods used in this research are qualitative methods and literature and research by recording, collecting, and analyzing reports. The results obtained from this study are that the company requires a computerized transaction recording system so that each sale or purchase transaction can assist management in making decisions. This is because information systems are an important part of managing and carrying out all activities in meeting the company's needs to handle various kinds of problems such as transaction processing and reporting. Thus, the right and quality decisions be made, which in turn increase sales and purchases. The benefits of computer-based information systems are a tool for companies and other organizations. Basically, companies need an accounting information system and the use of technology to produce information about the transactions the company carries out.